2020
DOI: 10.21203/rs.3.rs-97741/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ferulic Acid Alleviates Lipotoxicity-induced Hepatocellular Death Through SIRT1 Activating-regulated Autophagy Pathway, and Independently of AMPK and Akt in AML-12 Hepatocytes

Abstract: Background: Lipotoxicity-induced cell death plays a detrimental role in the pathogenesis of metabolic diseases. Ferulic acid, widespread in vegetative food, is conferred as a radical scavenger with multiple bioactivities. However, the benefits of Ferulic acid against hepatic lipotoxicity are largely unclear. Here, we investigated the protective role of ferulic acid on palmitate-induced lipotoxicity and clarify its potential mechanisms in AML-12 hepatocytes. Methods: AML-12 mouse hepatocyte was employed and exp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(86 reference statements)
0
0
0
Order By: Relevance
“…Lead acetate is a common ingredient in cosmetics, hair dyes, and plant protective chemicals. Xu et al (2021) conducted research that showed hydroxy-3methoxycinnamic acid can protect AML-12 hepatocytes from palmitate-induced lipotoxicity by reducing ROS accumulation. This reduction in ROS accumulation can lower the activation of proinflammatory cytokines such as IL-6 and IL-1β.…”
Section: -Hydroxy-3-methoxycinnamicmentioning
confidence: 99%
“…Lead acetate is a common ingredient in cosmetics, hair dyes, and plant protective chemicals. Xu et al (2021) conducted research that showed hydroxy-3methoxycinnamic acid can protect AML-12 hepatocytes from palmitate-induced lipotoxicity by reducing ROS accumulation. This reduction in ROS accumulation can lower the activation of proinflammatory cytokines such as IL-6 and IL-1β.…”
Section: -Hydroxy-3-methoxycinnamicmentioning
confidence: 99%